2007
DOI: 10.1007/s00436-007-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium parvum and Giardia duodenalis in healthy adult domestic ruminants

Abstract: To determine the prevalence and intensity of infection of Cryptosporidium spp. and Giardia duodenalis in healthy adult domestic ruminants, faecal samples were collected from 379 cattle of between 3 and 13 years old, 446 sheep and 116 goats selected at random from 60 dairy farms and 38 and 20 herds, respectively, in Galicia (NW Spain). Cryptosporidium spp. oocysts were detected in 32 cows (8.4%), 24 sheep (5.3%) and in nine goats (7.7%) from, respectively, 48.3% of the farms and 34.2 and 30.0% of the herds. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 41 publications
(59 reference statements)
7
57
3
3
Order By: Relevance
“…There were found to be Cryptosporidium oocysts in 111 (19.1 %) of the 582 goats examined. The parasite was detected in all the farms included in the study, but especially in the first and third of the ages considered, a finding which is in line with those reported by other authors (Matos-Fernández et al, 1993;Llamas Trujillo et al, 1994;Castro-Hermida et al, 2007). According to the semi-quantitative analysis carried out, our results showed the infection intensity decreased with age, being this similar to that found in goats by Noorden et al (2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were found to be Cryptosporidium oocysts in 111 (19.1 %) of the 582 goats examined. The parasite was detected in all the farms included in the study, but especially in the first and third of the ages considered, a finding which is in line with those reported by other authors (Matos-Fernández et al, 1993;Llamas Trujillo et al, 1994;Castro-Hermida et al, 2007). According to the semi-quantitative analysis carried out, our results showed the infection intensity decreased with age, being this similar to that found in goats by Noorden et al (2000).…”
Section: Discussionsupporting
confidence: 92%
“…Since then, the infection has been diagnosed in outbreaks of diarrhoea and prevalence in goat kids has been reported in several European countries (Majewska et al, 2000). In Spain Cryptosporidium infection in small ruminants was first diagnosed in 1985 (Rojo Vázquez et al, 1985); subsequently, cryptosporidiosis was reported from different geographical areas (Rojo Vázquez et al, 1987; Matos-Fernández et al, 1993;Castro-Hermida et al, 2007). Taking into account this background and its relevance, the aim of the present study was to estimate the prevalence in relation to age and kidding season of Cryptosporidium infection in goats at randomly selected farms in the southeast of Spain.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of positive samples (45% of analyzed animals and 84.6% of visited farms) showed the high occurrence of the parasite and possible environmental contamination due to the infected animals. Results reported in different countries show values ranging from 13 to 100% of properties contamination and 0.9 to 61% of parasite-infected calves, with high prevalence in Brazil (Wade et al, 2000;Fayer et al, 2006;Park et al, 2006;Castro-Hermida et al, 2007;Almeida et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…PCRs performed with fewer cysts (less than one per microscope field) lead to unsuccessful amplification due to the scantiness of genetic material extracted. 9 Floated material was transferred to the slide and examined by light microscopy. When cysts of G. duodenalis were observed, the slides were washed with 1 mL TE (10 mM Tris-HCL pH 8.0; 1 mM EDTA pH 8.0) in sterile Petri dishes.…”
Section: Molecular Characterizationmentioning
confidence: 99%